1971
DOI: 10.1159/000178234
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Plasma Inactivation of Thyrotropin Releasing Factor (TRF) and Related Peptides. Its Inhibition by Various Means and by the Synthetic Dipeptide PCA-His-OME

Abstract: Incubation in vitro of natural (ovine) or synthetic TRF (PCA-His-Pro-NH2) with rat blood, plasma, or reconstituted lyophilized serum destroys the biological activity. Inactivation of TRF by normal plasma takes place at 0 °C but at a slower rate than at 37 °C. Plasma obtained from rats several weeks after hypophysectomy and/ or hypophysectomy + thyroidectomy inactivates TRF. TRF activity is not recovered from TRF incubated in plasma when the incubate is treated with NaCl (4 m), ethanol (80% v/v) or H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1

Year Published

1973
1973
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 10 publications
4
15
1
Order By: Relevance
“…This value corresponds closely with current estimates of extracellular fluid volume in normal human subjects (11). The finding of a large TRH distribution volume is not unexpected in view of the small molecular size of TRH and the lack of evidence for binding of TRH to plasma protein (4,12).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This value corresponds closely with current estimates of extracellular fluid volume in normal human subjects (11). The finding of a large TRH distribution volume is not unexpected in view of the small molecular size of TRH and the lack of evidence for binding of TRH to plasma protein (4,12).…”
Section: Discussionsupporting
confidence: 86%
“…These results, plus the observations that TRH is inactivated Received for publication 21 November 1972 and in revised form 12 January 1973. rapidly by human plasma or serum in vitro (3,4), suggested that TRH rapidly disappears from the circulation in vivo. The present study was undertaken to determine the magnitude of plasma TRH concentrations that follow its intravenous administration and its rate of disappearance and metabolic fate.…”
Section: Introductionmentioning
confidence: 81%
“…'Grafted' and intact rats (120 g females) were injected with 25 ftCi ,2SI. Three days later they were transferred to a wellventilated and light-regulated hot room (35 ±0.5°C, 12 h light from 6 a.m. each day) for TRH studies [Vale et at.. 1971], The rats were housed in wire cages with elevated floors and given food and water ad lib. Starting 3 days after the elevation in ambient temperature and on successive days thereafter, TRH was injected into the conscious rat via the tail vein (dose range 3.3 to 270 ng TRH/rat).…”
Section: Methodsmentioning
confidence: 99%
“…Vials were counted for 10 min. TRH degraded was calculated by adding the radioactivity in the TRH sections and comparing it with that obtained from a control incubation with heat-inactivated serum (30 min, 55°C) (6)(7)(8). 90% of the applied radioactivity was recovere(I on the strips.…”
Section: Measurement Of Trh-degrading Activitymentioning
confidence: 99%